You can hide - Zanetti, Rebecca (Zanetti, Rebecca. Laurel Snow thriller, 2022)
When her newly discovered half-sister is linked to a series of dead bodies discovered in the Sauk River, FBI Special Agent Laurel Snow forms a risky alliance to catch a clever killer in an attempt to save her troubled sister's life, which might cost her own.